Designing Website At PT. Fanitra Indotama Using Macromedia Flash MX - Sugiarto Sugiarto; Marzuki Marzukim SKom., MMSI. (Jurnal Sistem Informasi, 2006)
PT. Fanitra Indotama is one company engaged in Cargo Courier service sector and Tour & Travel. Implementation of development in every sector continues to be, especially in the field of export import. This situation led to any related parties continued to clean himself preparing facilities and infrastructure as the backbone of successful development in all fields. Therefore, PT. Fanitra Indotama standing since March 30, 2000, present as partners in cooperation to meet the needs of the field of cargo courier.